Pengembangan Multimedia Berbasis Etnomatematika pada Siswa SMP - Kurniawan, Nashrudin; Yudi Purwoko, Riawan; Priyo Darminto, Bambang; Ika Purwaningsih, Wharyanti (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
This study aims to develop and determine the feasibility of ethnomathematics-based learning multimedia in junior high school students. This research used Research and Development methods with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). This research was conducted at Junior High School 19 Purworejo. The instruments used in this study were validation sheets, student questionnaire responses sheets, and test questions. The results of data analysis obtained from the assessment of media experts, learning and material on multimedia developed obtained an average rating of 3.63 with valid criteria. The results of the questionnaire data analysis of student responses to multimedia learning based on ethnomathematics obtained very practical criteria with a percentage of 81%. Learning multimedia is declared effective based on the effectiveness of the test results using the t-test; it can be concluded that there is a difference between before and after learning multimedia based on ethnomathematics. Thus, ethnomathematics-based learning multimedia developed in this study is categorized as suitable for mathematics learning in junior high school.